ANALYSIS DISCURSIVA ABOUT DYSLEXIA: ITS NUANCES AND THE DAMAGE CAUSED IN THE LEARNING PROCESS - Almeida, Josileide Eliodoro de; Coutinho, Diogenes José Gusmao (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
This study aims to make a discursive approach about dyslexia, its nuances and the damage caused in the learning process, as well as to show that teachers need to be aware that patients with this disorder have specific difficulties in cognitive processing and take a longer time and differentiated pace to learn. It was also seen with this research that the brain is not only able to produce new neurons, but also to respond to stimuli of the environment, with a learning that has to do with modifications linked to experience and modifications that are the expression of intentional plasticity. It can also be seen that the difficulty of learning is not an isolated situation and that, often, an evaluation and diagnosis of specialists are necessary for the treatment of disorders of this nature. Thus, family and school must walk together and the teacher be the mediator of the entire educational process for the success of dyslexic student learning.